Public Health-Herausforderung Hautkrebs und Sonnenschutzstrategien - Spähn, Bianca Annika; Görig, Tatiana; Diehl, Katharina (Public Health Forum, 2023)
Non-melanoma skin cancer is the most common form of cancer in Germany. Protection against ultraviolet (UV) radiation is considered the most important preventive measure. Qualitative data on the elderly population show deficits in current sun protection behavior, but awareness of the need for sun protection and the dangers of UV radiation seems to have increased over the years. For further education and prevention, regional and national sun protection strategies seem to be beneficial.
CRIS-Team Scopus Importer:2023-12-15
Keywords: non-melanoma skin cancer; sun protection behavior; UV radiation